Anti‐GAPDH Autoantibodies as a Pathogenic Determinant and Potential Biomarker of Neuropsychiatric Diseases. Issue 11 (9th October 2016) - Delunardo, Federica; Soldati, Denise; Bellisario, Veronica; Berry, Alessandra; Camerini, Serena; Crescenzi, Marco; Alessandri, Cristiano; Conti, Fabrizio; Ceccarelli, Fulvia; Francia, Ada; Valesini, Guido; Cirulli, Francesca; et al.
Abstract : Objective: To investigate the potential role of circulating autoantibodies specific to neuronal cell surface antigens in the pathophysiology of neuropsychiatric disorders. Methods: Two different kinds of immunoscreening approaches were used to identify autoantigens associated with neuropsychiatric disorders in the serum of patients with schizophrenia. The presence of autoantibodies specific to the identified autoantigens was then tested in patients with various psychiatric disorders and in patients with systemic lupus erythematosus (SLE) and concomitant neuropsychiatric manifestations. Furthermore, the potential pathogenic role of these autoantibodies was assessed both in vitro and in vivo. Results: GAPDH was identified as a novel autoantigen associated with neuropsychiatric disorders. Serum anti‐GAPDH IgG was detected in the serum of 51% of patients with schizophrenia and 50% of patients with major depression. Moreover, SLE patients with comorbid psychiatric manifestations presented significantly higher serum levels of anti‐GAPDH antibodies than did SLE patients without psychiatric manifestations ( P = 0.004 by chi‐square test). Of note, a significant positive correlation (R = 0.48, P = 0.0049, by Spearman's rank correlation test) was found between the levels of serum anti‐GAPDH antibodies and cognitive dysfunction in patients with SLE. In vitro analysis of the effects of purified human anti‐GAPDH autoantibodies on SH‐SY5Y cells showed an immediate neurite retraction. Finally, in vivo administration of anti‐GAPDH autoantibodies in the right cerebral ventricle of C57BL/6J mice resulted in specific behavioral changes associated with a detrimental cognitive and emotional profile. Conclusion: Overall, these data suggest that anti‐GAPDH autoantibodies play a role in the pathogenesis of neuropsychiatric disorders, thus representing a potentially promising tool for the screening of individual vulnerability to these disabling conditions.